Komunikasi Profetik dalam Pelayanan Jamaah Haji dan Umrah di Almira Travel: Pendekatan dan Tantangan - Hidayatullah, Syarif (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2019)
PT Almira Berkah Abadi, as a provider of Hajj and Umrah travel services, applies prophetic communication grounded in the values of tabligh (clear delivery), amanah (trustworthiness), and fathanah (wisdom). This study aims to analyze the implementation of prophetic communication in Hajj and Umrah services and identify the challenges faced by the company. Using the three-component service quality theory, this study evaluates the quality of outcomes, interactions, and the physical environment of the services provided. The findings reveal that the prophetic communication approach creates a meaningful worship experience for pilgrims, although challenges such as employee multitasking and regulatory changes persist. Strategic solutions, including employee training, technology utilization, and regulatory education, have been implemented to address these challenges.